Brief Presented to la commission des états généraux sur la situation et l'avenir de la langue française au Québec - The English Speaking Catholic Council (ESCC) (2001)
The English Speaking Catholic Council is a registered non-profit organization, made up of men and women from both the public and private sectors – all volunteers – who come together with a commitment to support and speak on behalf of their community in the fields of social justice, education, health and social services, and culture. In this year 2001, designated by the United Nations as the “International Year of Dialogue Among Civilizations”, the English Speaking Catholic Council comes before the Estates General with the hope of stimulating greater dialogue and understanding in a spirit of mutual respect among all people in Quebec.

Reasonable Accomodation and Freedom of Religion in Quebec - The English Speaking Catholic Council (ESCC) (2007)

Statement on Bill 21 : An Act Respecting the Laicity of the State - The English Speaking Catholic Council (ESCC) (2009)
The English Speaking Catholic Council (ESCC) was founded in 1981 with the mission to act as a catalyst, convener and facilitator of collective action for the English-speaking Catholic community of Quebec. As an organization inspired by Catholic social teaching, the Council is concerned for the common good and is apprehensive as to the implications of Bill 21 (An Act respecting the laicity of the State) for the social and civic welfare of Quebec society. In the main, the objections the Council have regarding the current legislation are similar to those we expressed in our 2013 brief on Bill 60 (Charter affirming the values of State secularism and religious neutrality and of equality between women and men, and providing a framework for accommodation requests)1 However, there are a number of critical differences between the 2013 legislation and that introduced in 2019.

Déclaration sur le projet de loi 21 : Loi sur la laïcité de l’État - The English Speaking Catholic Council (ESCC) (2009)
Le Conseil catholique d’expression anglaise a été fondé en 1981 avec la mission d'agir comme catalyseur, rassembleur et facilitateur de l'action collective pour la communauté catholique anglophone au Québec. En tant qu'organisme inspiré par l'enseignement social catholique, le Conseil se préoccupe du bien commun et s’inquiète donc des implications du projet de loi 21 (Loi sur la laïcité de l'État) pour le bien-être social et civique de la société québécoise. Pour l’essentiel, les objections du Conseil à l'égard de la législation actuelle sont semblables à celles que nous avons exprimées dans notre mémoire de 2013 sur le projet de loi 60 (Charte affirmant les valeurs de la laïcité d'État, de la neutralité religieuse et de l'égalité entre les femmes et les hommes, et fournissant un cadre pour les demandes d'accommodement).

Freedom of Religious Instruction : A Fundamental Right of Parents and Children - Murphy, Martin P.; The English Speaking Catholic Council (ESCC) (The English Speaking Catholic Council (ESCC), 2008)
From the time it was proposed in the late 19809s to shift the Quebec school system from a denominational model to a linguistic one, the English Speaking Catholic Council (ESCC) has consistently fought for freedom of religion and parental choice in religious instruction for people of all faiths. Time and again, the ESCC has defended these principles in its submissions to the National Assembly, the Commission for the Estates-General on Education, the Special Joint Committee of the House of Commons and the Senate, and most recently, the BouchardTaylor Commission on Reasonable Accommodation of Minorities.